'The remembering self': reflections on reconciliation and its absence - Leah, Gordon (Theology, 2015)
Referring initially to Sandor Marai’s novel, Embers, where a man seeks revenge for past wrongs rather than reconciliation, this piece maintains that reconciliation can result solely from complete remembrance of past hurt, then its confession and acceptance by victim and perpetrator. While humanity in resentment, pride and intransigence struggles and often fails to achieve this because remembrance of hurt is too strong, Christ through his free decision to reconcile the world to God offers reconciliation by his identification with the hurt of all parties, thus creating atonement. I consider Cain and Abel and Luke 15, theologians and lay scholars.